ANALISIS TAYANGAN iLOOK DI NET TV DALAM PEMENUHAN KEBUTUHAN FASHION PADA MAHASISWA UNDIKNAS DENPASAR - indah lestari; didik roy mahardika (Jurnal Ilmiah Dinamika Sosial, 2017)
ABSTRACTTelevision as a mass media which are as a device that has a major influence against the social life. One of the teens who were popular impressions of the moment is iLook served on Net Tv every Saturday and Sunday at 10.30 pm. iLook is a program that addresses a variety of ephemera related to appearance/style/fashion, from the toe to the tip of the head. The purpose of the concept of this event is to give new insights regarding the manner and style of dress model the present without reducing the limits of decency.This research is to know the fulfillment of the needs of fashion students at impressions iLook at the Net Tv, especially based on the analysis of the theory of uses and gratifications Undiknas students in Undiknas Denpasar. This thesis uses qualitative research methods as many as 10 informants. The results from this research was broadcast media like television no less interesting in some circles that has its own interests, for example Undiknas among the students on television is still one of the obligatory media they enjoy. This is supported by the theory uses and gratifications that researchers carefully at student Undiknas itself. Uses and Gratifications explained that the main problem is not how the media change the attitudes and the behavior of the audience, but how the media meet the needs of the social and private audiences.Keywords: iLook, Uses and Gratification, Fashion, Television